2005
DOI: 10.1002/meet.14504201178
|View full text |Cite
|
Sign up to set email alerts
|

Annotation as process: A vital information seeking activity in historical geographic research

Abstract: IntroductionAnnotations played a key role in the information-seeking process of an historical geographer, as observed during a nearly two-year collaboration. From the standpoint of an historical geographer's information requirements few studies appear to address this topic specifically --how do they become informed? Several resources touch upon issues related to historians' information behavior; describing the characteristics of source material (Brundage, 2002), research motives and methods (Case, 1991), histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…These annotations are made for different purposes, e.g. in the form of personal comments for scholars to structure and guide their thinking, in the form of tags or codes to analyse the edited sources and gather data, or in the form of links to other research materials to propose relevant relationships between the edited text and something else, be it another text, a photograph depicting an event described in the text or something else entirely (Boot et al 2017;Ruvane 2005).…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…These annotations are made for different purposes, e.g. in the form of personal comments for scholars to structure and guide their thinking, in the form of tags or codes to analyse the edited sources and gather data, or in the form of links to other research materials to propose relevant relationships between the edited text and something else, be it another text, a photograph depicting an event described in the text or something else entirely (Boot et al 2017;Ruvane 2005).…”
Section: Motivationmentioning
confidence: 99%
“…By third-party annotations, we mean annotations that contribute to the explanatory material already present on the edition's website, for the purpose of either private study or of publishing them alongside a scholarly article in which they are used, made by researchers unaffiliated with the edition project. Given the different purposes of annotations and the different forms that they can take, we adopt an inclusive view of annotation as an activity that can be part of almost any research activity, as also argued by Haslhofer et al (2009), Melgar (2016), Ruvane (2005) and Walkowksi (2017). This includes private as well as shared or public annotations.…”
Section: Motivationmentioning
confidence: 99%
“…Agosti and Ferro [1] and Haslhofer et al [6] showed how annotations created during reading can be used as metadata. Haslhofer et al [6], Ruvane [19] and Melgar [15] suggest a holistic view on annotation that is not limited to note-taking, but includes any form of metadata authoring (i.e., indexes, catalog records, tags, keywords, comments, notes), or even the creation of derivative documents or pieces of information derived from the initial information source. These annotations are created by any actor (expert or non-expert both in the domain and the annotation task) in the information interaction continuum, either during reading, information processing, or research.…”
Section: Annotations and Annotation Behaviourmentioning
confidence: 99%
“…Pre-corpus creation (8,9) Focused corpus selection (10) Exploratory search (4,6) Complementing corpus (11) Access and consultation (14,15) Interpretation (19) Answer RQ (20) …”
Section: (Iii) (A)mentioning
confidence: 99%
“…We cannot hope to study or analyse the detailed information behaviour, or practices, of each individual: although such studies have, in fact, been carried out, see for example Julien and Michels (2004) and Ruvane (2005). Therefore we study, and discuss the behaviour of groups: traditionally by occupation or academic discipline, more recently by role, demographic status, etc.…”
Section: Why Prioritise the 'Socialness' Of Information Behaviour?mentioning
confidence: 99%